UNVEILING WOMEN'S VOICES IN ASSAMESE FOLKLORE: A STUDY OF GENDER DYNAMICS AND RESISTANCE - Patgiri, Pritismita (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2024)
The focus of this paper is on the representation of women's voices in Assamese folklore. The status of women in society demonstrates how gender equality is reflected in all aspects of life. The struggles of women are attempted to be portrayed through Goalpariya Lokgeet, Jeng Bihu, and Biyanam. How Assamese women's resistance and hardships are reflected in folk songs. This paper tries to emphasize how folklore portrays their experience, identity, role, and problems. Lastly, it considers how important it is to raise women's voices to comprehend gender dynamics and resistance.